Molecular Phylogeny of Uropsilus (Talpidae, Eulipotyphla, Mammalia) With a New Species Described From Henan Province, China - Haijun Jiang; Yaohua Yang; Yanyan Zhou; Jundong Tian; Jiqi Lu (Ecology and Evolution)
ABSTRACT Shrew moles (Uropsilus), belonging to subfamily Uropsilinae of family Talpidae, were predominantly found in Myanmar, Vietnam, Bhutan, and Southwestern China. However, the extent distribution range of species within Uropsilus remains unclear. In 2022, we collected 18 specimens of Uropsilus from the western mountains of Henan Province in central China. Based on the mitochondrial (CYT B) and nuclear (RAG1 + RAG2) genes, the phylogenetic relationships, divergence times, and species delimitation of Uropsilus were analyzed. The results showed that the genetic distance of CYT B between new species and other species of Uropsilus ranged from 8.44% to 18.23%; the new species was a distinct valid species and speciated in the early Pleistocene (2.16 Ma, 95% CI = 2.00–2.65) based on phylogenetic analyses. Morphologically, the new species was distinguishable from the other species of Uropsilus by its yellowish–brown dorsum and ash‐black venter, short tail, slender and curved zygomatic arch, upper inward‐curved I1, and lack of a gap between I1 and I2. The combined results of morphological and molecular phylogenetic analysis indicated that the samples from Henan Province represented a new species—Uropsilus funiushanensis sp. nov. The specimens collected from the mountainous area of western Henan Province and Shennongjia in Hubei Province were identified as the same species. We suggested the evolutionary mechanism of the dental formula of U. funiushanensis and U. soricilus groups should be explored in the future.